High‐Performance Near‐Infrared Phototransistor Based on n‐Type Small‐Molecular Organic Semiconductor. (13th December 2016) - Li, Feng; Chen, Yin; Ma, Chun; Buttner, Ulrich; Leo, Karl; Wu, Tom
Abstract : A solution‐processed near‐infrared (NIR) organic phototransistor (OPT) based on n‐type organic small molecular material BODIPY‐BF2 has been successfully fabricated. Its unprecedented performance, as well as its easy fabrication and good stability, mark this BODIPY‐BF2 based OPT device as a very promising candidate for optoelectronic applications in the NIR regime.